The narrow application of the ecosystem services concept in EU policy - Kilgus, Jukka (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2026)
The ecosystem services concept (ES), describing the benefits humans derive from nature, has gained prominence during the last decades. There is, however, only very little research on how the concept has been translated into policy, one of the core reasons for its establishment. To address this gap, the present study examines the extent and variety of the ES concept’s usage in European Union policies since 2000. The study conducts qualitative content analysis of ten selected policy documents and background reports. The results show a rising, but typically ‘narrow’, use of the concept, which lacks depth in addressing critiques of ES approaches. This applies, in particular, to the underlying values and valuation methods. Here, the policies focus uniformly on instrumental values and monetary valuations, whereas other aspects, such as non-monetary valuations, are barely addressed. Apart from this, the contentiousness of the concept in the scientific literature is hardly recognisable in policy documents. These patterns are observable across the policies and background reports analysed and suggest either limited engagement due to formal constraints or a very particular and one-dimensional understanding of the concept by policymakers. Implications for future science-policy interactions in the field range from a call to increase the plurality of ES use to potentially adopting different concepts altogether, reflecting different societal paradigms for understanding human-nature relations.
Keywords: Ecosystem Services; European Union; Policy Analysis